2020
DOI: 10.1177/0092055x20980427
|View full text |Cite
|
Sign up to set email alerts
|

From Measures of Association to Multilevel Models: Sociology Journals and the Quantitative Literacy Gap

Abstract: While most sociology majors must take a statistics course, the content of this course varies widely across departments. Starting from the assumption that sociology students should be able to engage effectively with the sociological literature, this article examines the statistical techniques used in 2,804 journal articles—from four generalist sociology journals from 1990 to 2019 and 11 additional sociology journals from 2019—in order to assess which techniques have risen or fallen in prevalence. Although stalw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Level 1 articles could be read by "pretty much anyone [i.e., introductory students]… because they involve simple descriptive statistics, frequencies, and percentages" (Linneman 2021:52). Linneman (2021) found that 10 percent of quantitative articles published in 1990 fit this category, compared to a tiny four percent in 2019. These findings suggest renewed importance for sociology textbooks in the curriculum to bridge the gap between student skills and sociology published in journals.…”
Section: The Sociology Of Sociology Textbooksmentioning
confidence: 95%
See 1 more Smart Citation
“…Level 1 articles could be read by "pretty much anyone [i.e., introductory students]… because they involve simple descriptive statistics, frequencies, and percentages" (Linneman 2021:52). Linneman (2021) found that 10 percent of quantitative articles published in 1990 fit this category, compared to a tiny four percent in 2019. These findings suggest renewed importance for sociology textbooks in the curriculum to bridge the gap between student skills and sociology published in journals.…”
Section: The Sociology Of Sociology Textbooksmentioning
confidence: 95%
“…The sociology found in textbooks is critical to promoting student learning because of the increasing complexity of the sociology found in journals. For instance, Linneman (2021) analyzed the statistical techniques used in 15 sociology journals and found an expanding gap between the skills students learn in undergraduate statistics courses and what is published. Of interest to our study are those articles that Linneman (2021) categorized as Level 1.…”
Section: The Sociology Of Sociology Textbooksmentioning
confidence: 99%
“…Linneman (2021:52) categorized articles as Level 1 when they could be read by "pretty much anyone [i.e., introductory students]… because they involve simple descriptive statistics, frequencies, and percentages." Ten percent of quantitative articles published in 1990 fit this category, whereas only four percent did in 2019 (Linneman 2021).…”
Section: Data Visualization Literacymentioning
confidence: 98%
“…Thus, statistical information found in sociology textbooks, especially in introductory courses, is critical to promoting student learning and success with statistical information central to the profession (e.g., professional journal articles, applied sociology work). Furthermore, Linneman (2021) analyzed the statistical techniques used in 15 sociology journals and found an expanding gap between these techniques and the skills students learn in undergraduate statistics courses. Linneman (2021:52) categorized articles as Level 1 when they could be read by "pretty much anyone [i.e., introductory students]… because they involve simple descriptive statistics, frequencies, and percentages."…”
Section: Data Visualization Literacymentioning
confidence: 99%
See 1 more Smart Citation